Durable response rate as an endpoint in cancer immunotherapy: insights from oncolytic virus clinical trials. Issue 1 (19th September 2017) - Kaufman, Howard L.; Andtbacka, Robert H. I.; Collichio, Frances A.; Wolf, Michael; Zhao, Zhongyun; Shilkrut, Mark; Puzanov, Igor; Ross, Merrick
Abstract : Background: Traditional response criteria may be insufficient to characterize full clinical benefits of anticancer immunotherapies. Consequently, endpoints such as durable response rate (DRR; a continuous response [complete or partial objective response] beginning within 12 months of treatment and lasting ≥6 months) have been employed. There has not, however, been validation that DRR correlates with other more traditional endpoints of clinical benefit such as overall survival. Methods: We evaluated whether DRR was associated with clinically meaningful measures of benefit (eg, overall survival [OS], quality of life [QoL], or treatment-free interval [TFI]) in a phase 3 clinical trial of an oncolytic virus for melanoma treatment. To evaluate the association between DRR and OS and to mitigate lead time bias, landmark analyses were used. QoL was evaluated using the FACT-BRM questionnaire (comprising the FACT-BRM Physical, Social/Family, Emotional, and Functional well-being domains, the Additional Concerns, Physical and Mental treatment-specific subscales, and the Trial Outcome Index [TOI]). TFI was defined as time from the last study therapy dose to first subsequent therapy dose (including any systemic anticancer therapy for melanoma after study therapy discontinuation). Results: Four hundred thirty-six patients were included in the intent-to-treat population. Achieving DR was associated with a statistically significant improvement in OS in a landmark analysis at 9 months (HR = 0.07; P = 0.0003), 12 months (HR = 0.05, P < 0.0001), and 18 months (HR = 0.11; P = 0.0002) that persisted after adjusting for disease stage and line of therapy. Achieving a DR was associated with a longer median TFI (HR = 0.33; P = 0.0007) and a higher TOI improvement rate (58.1% versus 30.0%; P = 0.025). Conclusions: Achieving a DR was associated with clinical benefits such as improved OS and QoL and prolonged TFI, thus supporting the usefulness of DR as a meaningful immunotherapy clinical trial endpoint. Trial registration: ClinicalTrials.gov identifier, NCT00769704 (https://clinicaltrials.gov/ct2/show/NCT00769704 ) October 7, 2008